Horti Bank: the Concept of Agricultural Financing Through Farmer Group Synergy to Increase the Welfare of Horticultural Farmers Affected by Covid-19 in East Java - Ahmad Burhanudin; Adinda Permatasari; Safira Ummah (East Java Economic Journal, 2020)
The COVID-19 pandemic (Corona Virus Disease 2019) is considered a global pandemic by WHO (World Health Organization) and its spread has reached Indonesia. The COVID-19 pandemic has an impact on national economic growth which causes a decline and also causes an economic downturn. This Pandemic also caused an economic downturn experienced by the Province of East Java which had a relatively large number of cases. The agricultural sector is present as a resilient sector that can survive the COVID-19 pandemic which can contribute to supporting the economic growth rate of East Java. The agricultural sector consists of several sub-sectors, one of which is the horticultural crop sub-sector which has high potential. There are many obstacles experienced by horticultural farmers in their farming. The purpose of this study is to determine the problems experienced by horticultural farmers in East Java Province and to form an institutional model as a solution to the problem to improve the welfare of horticultural farmers in East Java Province through increasing NTP (Farmer Exchange Rate). Analytical descriptive method, case study method and literature study were used in this research. The results showed that (1) the problems experienced by farmers were (a) horticultural farmers generally have a relatively small capacity to provide capital; (b) Sales of horticultural crops are only made to middlemen; (c) Low accessibility to local financing institutions; (d) Agricultural financing credit system that is too burdensome for farmers; (e) There is a gap between farmers and financial institutions; (f) Credit by formal institutions is prioritized in the non-agricultural sector; (2) The existence of the "Horti Bank" institution which is implemented will help in overcoming the problems of horticultural farmers in East Java Province by providing facilities in the form of capital loans with the concept of investment, managing finances, and providing access to insurance for horticultural farmers in East Java Province; (3) The simulation results show that the existence of a Horti Bank can increase the exchange rate of farmers so that it is expected to reduce poverty in East Java.